PENINGKATAN PENGUASAAN KONSEP PADA MATERI POKOK HIDROKARBON MELALUI PEMBELAJARAN PENEMUAN TERBIMBING - Rohmawati Rohmawati; Tasviri Efkar; Nina Kadaritna (Jurnal Pendidikan dan Pembelajaran Kimia, 2013)
The objective of this research is to describe the effectiveness of guided discovery learning in improving concept mastery in hydrocarbon material.  The guided discovery learning consists of 3 phases; they are exploration, discovery and concept application, and evaluation.  Population in this research was all 360 Grade X students in State Senior High School 12 in Bandar Lampung in academic year 2011-2012 which were distributed in 10 classrooms; from classroom X1 to X10. Classroom X5 and X10 were used as samples which were collected with purposive sampling.  This research used quasi experiment method and non equivalent control group design.  Effectiveness of guided discovery learning was measured based on N-Gain values.  The results showed that the classroom with guided discovery learning possessed higher concept mastery than classrooms with conventional learning.  The averages of N-Gain values for student’s concept mastery for experiment and control classrooms were 0.539 and 0.402 respectively.   This indicated that the guided discovery learning was more effective in improving student’s concept mastery in hydrocarbon material.   Kata kunci:         pembelajaran penemuan terbimbing, penguasaan konsep,    hidrokarbon